2022
DOI: 10.1051/0004-6361/202243545
|View full text |Cite
|
Sign up to set email alerts
|

Photometric detection of internal gravity waves in upper main-sequence stars

Abstract: Context. Recent studies of massive stars using high-precision space photometry have revealed that they commonly exhibit stochastic low-frequency (SLF) variability. This has been interpreted as being caused by internal gravity waves (IGWs) excited at the interface of convective and radiative regions within stellar interiors, such as the convective core or sub-surface convection zones, or caused by dynamic turbulence excited in the sub-surface convection zones within the envelopes of main-sequence massive stars.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…The high-frequency tail above the peak frequency in our signal looks very similar to an already widely discussed characteristic signal in hot massive stars, commonly referred to as the SLF variability or red noise (Bowman et al 2019b(Bowman et al , 2019a(Bowman et al , 2020Szewczuk et al 2021;Bowman & Dorn-Wallenstein 2022;Dorn-Wallenstein et al 2022). We note that, however, the signal pattern in our sample is distinct as it has decaying power toward zero frequency, while the red noise signal mostly concerns the high-frequency tail.…”
Section: Universal Signal In Bsgssupporting
confidence: 81%
“…The high-frequency tail above the peak frequency in our signal looks very similar to an already widely discussed characteristic signal in hot massive stars, commonly referred to as the SLF variability or red noise (Bowman et al 2019b(Bowman et al , 2019a(Bowman et al , 2020Szewczuk et al 2021;Bowman & Dorn-Wallenstein 2022;Dorn-Wallenstein et al 2022). We note that, however, the signal pattern in our sample is distinct as it has decaying power toward zero frequency, while the red noise signal mostly concerns the high-frequency tail.…”
Section: Universal Signal In Bsgssupporting
confidence: 81%
“…While we have shown the photometric variability from convectively excited gravity waves is not directly detectable, these waves may mix chemicals 46 or transport angular momentum 26 , leading to observable signals in more traditional g-mode asteroseismology 9 , 47 , 48 . Even though the red noise signal is not the surface manifestation of gravity waves, it still carries valuable information about both the near-surface structure of massive stars as well as their masses and ages 15 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that photometric light curves of hot, massive stars contain a ubiquitous red noise signal 13 18 . Theories for the driving mechanism of red noise include gravity waves stochastically excited by core convection, or turbulence from subsurface convection zones 14 , 19 , 20 .…”
Section: Mainmentioning
confidence: 99%
“…Although two-and three-dimensional hydrodynamical simulations of IGWs for massive stars with M > 8 M e have also been done (e.g., Herwig et al 2023;Ratnasingam et al 2023;Thompson et al 2023), the influence of magnetic fields on these stars is still not widely studied. Stochastic low-frequency (SLF) variability is observed in upper-mainsequence stars (e.g., Bowman et al 2019aBowman et al , 2019bBowman et al , 2020Bowman & Dorn-Wallenstein 2022). SLF variability is seen across a wide range in mass, age, and metallicity in massive stars (Bowman et al 2020(Bowman et al , 2019b.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of SLF variability is currently under debate. It could be caused by the IGWs (e.g., Bowman et al 2019aBowman et al , 2020Edelmann et al 2019;Bowman & Dorn-Wallenstein 2022), or by subsurface convection zones (e.g., Blomme et al 2011;Cantiello & Braithwaite 2019;Lecoanet et al 2019;Cantiello et al 2021). Bowman et al (2019b) investigated the 167 OB-type stars within the Milky Way and Large Magellanic Cloud, and reported that SLF variability is insensitive to the metallicity of the star.…”
Section: Introductionmentioning
confidence: 99%